Phân vị địa tầng mới - Hệ tầng Bình Đại, tuổi Holocen sớm vùng cửa sông ven biển Châu thổ Sông Cửu Long - Dỹ, Nguyễn Địch; Lâm, Doãn Đình; Hà, Vũ Văn; Tấn, Nguyễn Trọng; Tuấn, Đặng Minh; Quảng, Nguyễn Minh; Cúc, Nguyễn Thị Thu (Vietnam Journal of Earth Sciences, 2012)
SummaryNew stratigraphic unit - The Early Holocene Binh Dai formation at the Estuary and coastal area of Cuu Long deltaThe Binh Dai Formation was established by analysis results of the BT3 borehole of KC09.06/06- 10 project, in Ba Tri commune - Binh Dai district of Ben Tre province. The sedimentary of Binh Dai Formation has identified Early Holocene age that was formed at the coastal estuarine environment(amQ21bd ), distributed inside the borehole at the depth from 34m to 53m.The Binh Dai formation (Q22lm ) overlain unconformably over the Long My formation (Q23lm) and covered by the sediments of the Hau Giang formation (Q22hg).